Obesity among children aged 10-13 years in public and private elementary schools - Evi Kamelia; Nurdiani Nurdiani; Tiansa Sembiring; Hakimi Hakimi; Iskandar Z Lubis (Indonesian Pediatric Society Publishing House, 2016)
Background In the last few years, the prevalence of obesity among Indonesian children has been beginning to increase slowly, but studies and publications about obesity are limited. In accordance with the improvement of social economic and child health, obesity can be seen more frequently as a problem in children. Objective To evaluate and compare the prevalence and related factors of obesity among children 10-13 year-old who were stu- dents of two kinds of school, namely public and private elementary school. Methods A cross sectional study was done from October until December 1995 on 276 elementary school students aged 10-13 years consisting of 138 public and 138 private elementary school students. Data were collected by a questionnaire including anam- nesis of family history and type of daily diet, physical examination, and anthropometric measurement. Results The prevalence of obesity among children in the public and private elementary schools was 9% and 20% respectively, which showed a significant difference (p<0.01). The prevalence of obesity among children was significantly related to parents' wel- fare, excessive daily calorie intake, level of physical activity, and obesity problem in the family. Conclusion The prevalence of obesity in students of private and public elementary schools was 20% and 9% respectively. Social economic level, calorie intake, sport activities, and obesity prob- lems in the family are factors related to the prevalence of child obesity